An extended engineering critical assessment for corrosion fatigue of subsea pipeline steels. (February 2018) - Cheng, Ankang; Chen, Nian-Zhong
Abstract: Engineering critical assessment (ECA) is widely used to assess the structural integrity in offshore industry. But industry standards provide limited guidance on ECAs of structures subjected to corrosion fatigue (CF). In this paper, a critical stress intensity factor (SIF) derived from a corrosion-crack correlation model is proposed to improve the traditional ECA for steel structures in seawater. The proposed critical SIF extends the traditional ECA for CF in that it accounts for the influence of load frequency and initial crack size on the model selection within current ECA guidelines for the ECA of marine structures under CF. The extended ECA is applied for × 65 carbon pipeline steels subjected to CF. The crack growth curves are built using a three-stage CF crack growth model and the experimental data. Fatigue lives are calculated based on those curves as well as traditional ECA models. Results show that the critical SIF can effectively improve the ECA for × 65 carbon pipeline steels under CF. The extended ECA provides a reasonable assessment with reduced conservatism in contrast to the traditional ECA for CF. Highlights: A critical stress intensity factor was proposed for the engineering critical assessment of corrosion fatigue. The factor extended the traditional assessment to consider the influence of load frequency and initial crack size. The extended assessment provides reasonable results with significantly reduced conservatism.